Genetic Analysis of Resistance to Brown Planthopper in Rice (Oryza sativa L.) - Kabis, Anwarul; Khush, G.S. (Wiley, 1988)
Seventeen rice cultivate resistant to brown planthoppers were genetically analyzed using the Bangladesh insect population. Seven cultivars were found to have a single dominant gene for resistance. These genes segregated independently of the recessive resistance gene bph‐5. Tae dominant resistance gene of ‘Swarnalata’ was designated Bph‐6. In ten cultivars, resistance is conferred by single recessive genes. In eight cultivars, the resistance genes are allelic to bph‐5. However, the recessive genes o: two cultivars are non‐allelic to bph‐5. The recessive gene of T12 is designated bph‐7.